2013
DOI: 10.1007/s12013-013-9778-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Abrogates the Cardioprotection of Ischemic Postconditioning in Isolated Rat Heart: Roles of Glycogen Synthase Kinase-3β and the Mitochondrial Permeability Transition Pore

Abstract: Ischemic postconditioning (IPO) reduces lethal reperfusion injury under normal conditions, but its effectiveness in hypercholesterolemia (HC) is disputed. We measured the cardioprotection of IPO in hypercholesterolemic rats and determined the roles of glycogen synthase kinase-3β (GSK-3β) and the mitochondrial permeability transition pore (mPTP). Isolated rat hearts underwent 30-min global ischemia and 120-min reperfusion. Postconditioning protocol induced six cycles of 10s ischemia and 10s reperfusion at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
3
27
0
4
Order By: Relevance
“…For example, Prasan et al (14) demonstrated that NO production is decreased in the hearts of hypercholesterolemic rabbits during I/R, and Schwemmer et al (29) detected decreased cGMP levels in the hearts of hypercholesterolemic guinea pigs. Furthermore, previous studies have also demonstrated that cardioprotective mechanisms, such as preconditioning and postconditioning, in which the NO/sGC pathway has an important role, are abolished in hyperlipidemia (16)(17)(18). Therefore, we hypothesize that NO donors may have induced cardioprotection against I/R injury in hypercholesterolemic hearts.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, Prasan et al (14) demonstrated that NO production is decreased in the hearts of hypercholesterolemic rabbits during I/R, and Schwemmer et al (29) detected decreased cGMP levels in the hearts of hypercholesterolemic guinea pigs. Furthermore, previous studies have also demonstrated that cardioprotective mechanisms, such as preconditioning and postconditioning, in which the NO/sGC pathway has an important role, are abolished in hyperlipidemia (16)(17)(18). Therefore, we hypothesize that NO donors may have induced cardioprotection against I/R injury in hypercholesterolemic hearts.…”
Section: Discussionmentioning
confidence: 71%
“…The infarct size was determined as previously described (17). Briefly, after 120 min of reperfusion, the hearts were harvested.…”
Section: Induction Of Experimental Hypercholesterolemiamentioning
confidence: 99%
See 1 more Smart Citation
“…В 2014 г. китайские кардиологи опубликовали резуль-таты своих экспериментов на изолированных сердцах крыс с гиперхолестеринемией и здоровых особей [9]. Изолированные сердца подвергали глобальной ишемии (30 мин) и реперфузии (2 ч).…”
Section: экспериментальные данныеunclassified
“…Посткондиционирование способство-вало уменьшению индекса ЗИ/ОР в 2 раза, количества апоптозных кардиомиоцитов -в 3 раза. Гиперхолесте-ринемия устраняла инфаркт-лимитирующий и антиапоп-тотический эффект посткондиционирования [9]. Свои данные авторы подтвердили в том же году еще раз [10]: в опытах на изолированных сердцах крыс с дислипидемией они установили, что добавление в перфузионный раствор фасудила -ингибитора Rho-киназы (Ras homologs -группа белков, родственных белку Ras) -восстанавли-вает инфаркт-лимитирующий эффект адаптации к репер-фузии [10].…”
Section: экспериментальные данныеunclassified